2022
DOI: 10.1136/bmjopen-2021-056229
|View full text |Cite
|
Sign up to set email alerts
|

Examining the association between reported COVID-19 symptoms and testing for COVID-19 in Canada: a cross-sectional survey

Abstract: ObjectivesStudies on the management of the COVID-19 pandemic through testing have been conducted in countries that have been hardest hit by this pandemic. Considering the importance of testing in containing the spread of COVID-19, it is useful to have evidence on continuing COVID-19 testing even in countries where the prevalence of COVID-19 is relatively low. We, therefore, examined the association between reported COVID-19 symptoms and testing for COVID-19 in Canada.Design and settingsWe conducted an online s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Two studies reported on disparities in COVID-19 screening. 35 , 36 In a cross-sectional study, Pongou et al 36 found that the prevalence of being tested for COVID-19 across reported COVID-19 symptoms was far lower among Black Canadians (8.46%) than among those who were White (17.30%), mixed race/ethnicity (28.41%) or from another ethnoracial group (27.37%), although the differences were not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported on disparities in COVID-19 screening. 35 , 36 In a cross-sectional study, Pongou et al 36 found that the prevalence of being tested for COVID-19 across reported COVID-19 symptoms was far lower among Black Canadians (8.46%) than among those who were White (17.30%), mixed race/ethnicity (28.41%) or from another ethnoracial group (27.37%), although the differences were not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies examined high rates of COVID-19 infection among Black Canadians. 36 - 39 A quantitative study indicated that higher numbers of COVID-19 cases are associated with socioeconomic factors such as race and housing. For instance, of all marginalized groups in Montral, Quebec, the strongest relationship with positive COVID-19 cases occurred among those living in overcrowded housing and in boroughs with high proportions of Black people.…”
Section: Resultsmentioning
confidence: 99%
“…With the closures of schools, childcare may have fallen disproportionately to females, necessitating more time in the home and reducing social contacts. The risk for males in the workplace may be different from that of females ( 41 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…A mixed cross-sectional survey study was used to investigate the short-term impacts of COVID-19 in Guinea. The survey instrument was adapted from Canning et al (2020) and Pongou et al (2022). Both qualitative and quantitative questions were included in the survey, to collect descriptive data on the sociodemographic characteristics of participants as well as symptoms of COVID-19, work experience, loss of income, education, mental health, social distancing behavior, COVID-19 testing and vaccination.…”
Section: Methodsmentioning
confidence: 99%